Implementasi Manajemen Keselamatan Pasien (Patient Safety) Dalam Usaha Pencegahan Medication Error Di RSUD Dr. Moewardi Tahun 2015 - Hanawati Haryanto Putri, Yuniar; , Sri Sugiarsi, SKM, M.Kes; , Kusuma Estu Werdani, SKM., M.Kes (2015)
Medication error is one the measure of patient safety achievement. The medication errors at Dr. Moewardi Hospital in terms of quantity is in top rank. This will be a problem in the implementation of patient safety management. The role of the hospital management is needed to achieve the goals set. The aim of this study was to analyze the implementation of the patient safety management on preventing of medication errors that refers to the seven steps to patient safety. The type and design of this study is a qualitative study with critical incident approach. The informant in this study consists of three main informants and 2 informers triangulation with purposive sampling technique in determining the informants. The results of the research showed that the implementation of the patient safety management on preventing medication errors at Dr. Moewardi Hospital has already performed well. But there are weaknesses in the way of determining the different grading between teams of patient safety and pharmacy. The team only reported patient safety incidents just to the RCA and to KKP-RS PERSI, and there is no reward for staff who dares to report the incident. Key word : patient safety achievement, medication error, Dr. Moewardi Hospital.